Multilayer airdrome pavement modeling on the base of numeically-analythical method of potential - Шевченко, О.М. (Proceedings of National Aviation University (archive), 2004)
There are problems of the take into account the multilayered foundation distributive properties which are ignored in the elementary case of Winkler foundation at calculation of constructions on the elastic foundation. In article the apparatus realization of numerically-analytical method of potential for a problem about stress and strain state analysis is considered for the multilayered pavement consisting from two isotropic layers with a separating layer between.